Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12889-021-10353-3
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of knowledge, attitude and practice (KAP) towards COVID-19 pandemic among the Syrian residents

Abstract: Background Effective COVID-19 pandemic management requires adequate understanding of factors that influence behavioral changes. This study aims to assess knowledge, attitudes and practices towards COVID-19 among Syrians in a post-conflict context. Method A cross sectional web-based survey was conducted on the Syrian residents of 16 years and above. It contains questions on knowledge, attitudes and practices (KAP) with respect to COVID-19. Participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
55
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 19 publications
20
55
7
Order By: Relevance
“…However, not all the studies coincided with the age of greatest acceptance; thus, as opposed to our study, the groups which showed the greatest rejection were those older than 75 years old, despite being a very vulnerable age group [ 30 ]. The type of employment did not have an influence on vaccine rejection; however, a lower level of education was associated with the rejection of vaccines, as previously described in other studies conducted in Syria and Australia [ 32 , 33 , 34 ]. There was evidence that political leanings played an important role on the attitude associated to vaccines.…”
Section: Discussionsupporting
confidence: 74%
“…However, not all the studies coincided with the age of greatest acceptance; thus, as opposed to our study, the groups which showed the greatest rejection were those older than 75 years old, despite being a very vulnerable age group [ 30 ]. The type of employment did not have an influence on vaccine rejection; however, a lower level of education was associated with the rejection of vaccines, as previously described in other studies conducted in Syria and Australia [ 32 , 33 , 34 ]. There was evidence that political leanings played an important role on the attitude associated to vaccines.…”
Section: Discussionsupporting
confidence: 74%
“…On the contrary, Gao et al (2020) showed that the respondent in China had good practice regarding COVID-19 prevention, similar to the respondent in Uganda (Okello et al, 2020) and Malaysia (Azlan et al, 2020). The reason might be that the respondent has good knowledge and a positive attitude that applied into good practice (Ahdab, 2021;Gao et al, 2020;Lee et al, 2021). This represents a willingness for respondents to make behavioural changes during the COVID-19 pandemic (Azlan et al, 2020).…”
Section: Practice Toward Covid-19 Preventionmentioning
confidence: 94%
“…This is possible because the belief can pass this situation and win against the disease by supporting lockdown decision and following restrictive policies (Kartheek et al, 2020). Efficacy beliefs had a significant and robust impact on practising preventive behaviours, implying promoting preventive behaviours toward COVID-19 (Ahdab, 2021;Azlan et al, 2020;Lee et al, 2021;Okello et al, 2020 (Gao et al, 2020). Other studies showed that it might be because the availability of hand washing facilities (Lau et al, 2020;Mohamed et al, 2021).…”
Section: Attitude Toward Covid-19 Preventionmentioning
confidence: 96%
See 1 more Smart Citation
“…Good knowledge, attitudes, and practices (KAPs) targeted toward certain diseases or infections among the public are essential for successful control and outbreak prevention of pandemics (15,16). However, efforts to better define KAPs in hunters have been scarce, and mainly limited to Canada and the United States of America (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%